Burnout and study engagement among medical students during COVID-19 pandemic: A cross-sectional study in Aceh, Indonesia - Al-Gunaid, Seba; Syukri, Maimun; Kurniawan , Ferry D.; Rizal, Syamsul; Novirianthy, Rima (Narra X, 2025)
Medical students are particularly vulnerable to burnout due to the demanding and resource-constrained nature of their training. Burnout negatively impacts academic and personal well-being, potentially impacting future professional practice and patient care. To date, no studies have examined burnout prevalence among medical students in Aceh. The aim of this study was to determine the association between burnout and academic engagement among medical students at Syiah Kuala University, as well as the relationship with age, sex, and year of study. This cross-sectional study was conducted among medical students in Aceh, Indonesia, between October 1, 2021, and March 13, 2022. Total sampling was employed to select study participants. Data were collected using an e-questionnaire using the Oldenburg Burnout Inventory questionnaire adapted for students (OLBI-S) and Utrecht Work Engagement Scale for Students (UWES-S-9) for academic engagement. The total number of participants was 286 students. Most participants were female (n=202, 70.6%), while male students were 84 (29.3%). The prevalence of burnout was 36% (n=102). Gender (p=0.65) and study year (p=0.62) were not associated with disengagement, a subscale of the OLBI-S. Similarly, exhaustion scores did not differ significantly by gender (p=0.48) or study year (p=0.28). In conclusion, fewer than half of the medical students experienced burnout during the COVID-19 pandemic, with no association found between burnout and gender or study year.